Plate waste and malnutrition in intensive care patients - Karlı, Kevser; Sarıaslan, Mehtap; Tümer, Güzin (Turkish Society of Clinical Enteral and Parenteral Nutrition, 2024)
Objective: This study aimed to determine food waste rates in intensive care patients. Methods: In this cross-sectional study, 45 patients in the intensive care unit were assessed for malnutrition risk using NRS 2002. Food waste rates were calculated by weighing the weight of the food served and left on the plate. Energy density of foods was calculated. The patients’ energy and nutrient intakes were calculated. Evaluated according to the recommendations of the Türkiye Dietary Guidelines. Results: 55.55% of the patients had severe malnutrition. Patients cannot consume 38.17% of the food served. The highest waste rate is in vegetables and salads (75.35%). The energy density of patients’ food consumption is low. The patients’ energy and protein intake was 828.56 kcal/day and 32.13 g/day. Energy and nutrient intake are below recommended, except for sodium and vitamin B12. A moderate positive correlation was found between hand grip strength and energy (r=413, p=0.001) and protein (r=453, p=0.001) intake. Conclusion: Patients cannot consume approximately 40% of the food. Improved protein and energy intake increased muscle strength and performance. Since a decrease in food intake will cause malnutrition to worsen, there is a need to develop strategies to increase energy and protein intake in these patients.
Keywords: 2. Zero hunger; 3. Good health